Sensory neuropathy-causing mutations in ATL3 affect ER–mitochondria contact sites and impair axonal mitochondrial distribution. (18th October 2018) - Krols, Michiel; Asselbergh, Bob; De Rycke, Riet; De Winter, Vicky; Seyer, Alexandre; Müller, Franz-Josef; Kurth, Ingo; Bultynck, Geert; Timmerman, Vincent; Janssens, Sophie
Abstract: Axonopathies are neurodegenerative disorders caused by axonal degeneration, affecting predominantly the longest neurons. Several of these axonopathies are caused by genetic defects in proteins involved in the shaping and dynamics of the endoplasmic reticulum (ER); however, it is unclear how these defects impinge on neuronal survival. Given its central and widespread position within a cell, the ER is a pivotal player in inter-organelle communication. Here, we demonstrate that defects in the ER fusion protein ATL3, which were identified in patients suffering from hereditary sensory and autonomic neuropathy, result in an increased number of ER–mitochondria contact sites both in HeLa cells and in patient-derived fibroblasts. This increased contact is reflected in higher phospholipid metabolism, upregulated autophagy and augmented Ca 2+ crosstalk between both organelles. Moreover, the mitochondria in these cells display lowered motility, and the number of axonal mitochondria in neurons expressing disease-causing mutations in ATL3 is strongly decreased. These results underscore the functional interdependence of subcellular organelles in health and disease and show that disorders caused by ER-shaping defects are more complex than previously assumed.